Estudos in sı́lico de proteı́nas alostéricas e sua interação com ligantes - Freire, Thales Souza (Universidade Federal de São Carlos, 2023)
Allosteric proteins are extremely important for the regulation of several functions in the organism, such as the transport of molecules through the blood and cell membranes, as well as the phosphorylation of other proteins. In this context, the present work was divided into the study of three proteins: Abelson Tyrosine Kinase (Abl1), Human Serum Albumin (HSA) and FMS-Like Tyrosine Kinase 3 (FLT3). Each protein was studied separately, using computational simulation methods, such as Classical Molecular Dynamics and Molecular Docking. For Abl1 was studied the emergence of resistance to the drug dasatinib upon mutations. Here, three mutations were simulated with the Free Energy Perturbation method, where the difference in free energy variation between binding the inhibitor to the native and mutant form of the enzyme was calculated, obtaining a good agreement with experimental values. As for albumin, the change in conformation mediated by the interaction with medium-chain fatty acids was studied. In this case, the well- tempered Metadynamics method was used to facilitate the transition between states and obtain the path of minimum free energy between one state and another, the results were compatible with the experimental observations. As for FLT3, a study similar to that of Abl1 was initiated, for the drug gilteritinib, however the dynamics of this enzyme proved to be more complex than that of Abl1. As the theoretical results did not agree with the experimental values, it was decided to investigate the effect of mutations on the activation free energy profile, using Metadynamics with collective path variables. Such a tool made it possible to reveal the effect of mutations on the activation dynamics, where the resistance effect is partly due to a reduction in the enzyme activation barrier. In the three cases, pure molecular dynamics alone was not able to give the desired information, making it necessary to resort to enhanced sampling methods, such as free energy perturbation and metadynamics, which showed to be efficient for the treated cases.
In silico studies of allosteric proteins and their interaction with ligands
Keywords: Alosteria; Proteı́nas; Enzimas; Dinâmica molecular; Metadi-nâmica; Perturbação de energia livre; Mutações; FLT3; Abl1; HSA; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA GERAL::FISICA ESTATISTICA E TERMODINAMICA